Find your Math Personality!

X Squared

X Squared

In this mini-lesson, we will explore what is x squared, the difference of squares, and solving quadratic by completing the squares.

In algebra, we commonly come across the term x squared. Do you aware of what is x squared?

What is x squared?

We are going to learn particularly about \(x^2\) in this mini-lesson.

Lesson Plan

What is x squared?

x squared is a notation that is used to represent the expression \(x\times x\).

i.e., x squared equals x multiplied by itself.

In algebra, \(x\) multiplied by \(x\) can be written as \(x\times x\) (or) \(x\cdot x\) (or) \(x\, x\) (or) \(x(x)\)

\(x\) squared symbol is \(x^2\).


  • \(x\) is called the base.
  • 2 is called the exponent.
\(x\) squared = \(x^2\) = \(x\times x\)

Here are some examples to understand \(x\) squared better.

Phrase Expression

x squared times x

\(x^2\times x =x^3\)

x squared minus x


x squared divided by x

\(x^2\div x =x^1=x\)

x squared times x squared

\(x^2\times x^2 =x^4\)

x squared plus x squared

\(x^2+x^2 =2x^2\)

x squared plus y squared

square root x2


x squared times x cubed

\(x^2\times x^3 =x^5\)

important notes to remember
Important Notes
  1. Here we use the laws of exponents in case of multiplying or dividing the exponents of the same base. 
    x^{m} \cdot x^{n} &=x^{m+n} \\
    \frac{x^{m}}{x^{n}} &=x^{m-n}
  2. The formulas for the squares of the sum and the difference are:
    (x+y)^{2}=x^{2}+2 x y+y^{2} \\
    (x-y)^{2}=x^{2}-2 x y+y^{2}

Is x Squared Same as 2x?

No, \(x^2\) is NOT same as \(x\).

Using the exponents, \(x^2 = x \times x \).

But \(2x = 2 \times x= x + x\), because multiplication is nothing but the repeated addition.

Is x squared same as 2x?

Here are some examples to understand it better.


\(x^2 = x \times x\) \(2x = 2 \times x\)

\(3 \times 3=9\)

2(3) = 6

\(-1 \times -1 = 1\)

2(-1) = -2

\(-2 \times -2 =4\)

2(-2) = -4

Special Factoring: Difference of Squares

While factoring algebraic expressions, we may come across an expression that is a difference of squares.

i.e., an expression of the form \(x^2-y^2\).

There is a special formula to factorize this:


Here are some examples to understand it better.









Solving Quadratics by Completing the Square

Completing the square in a quadratic expression \(ax^2+bx+c\) means expressing it of the form \(a(x+d)^2+e\).

Introduction to how to complete the square is explained using a quadratic equation.

Let us learn how to complete a square using an example.


Complete the square in the expression

\[-4 x^{2}-8 x-12\]


First, we should make sure that the coefficient of \(x^2\) is \(1\)

If the coefficient of \(x^2\) is NOT \(1\), we will place the number outside as a common factor.

We will get:

\[-4 x^{2}-8 x-12 = -4 (x^2+2x+3)\]

Now, the coefficient of \(x^2\) is \(1\)

Step 1: Find half of the coefficient of \(x\)

Here, the coefficient of \(x\) is \(2\)

Half of \(2\) is \(1\)

Step 2: Find the square of the above number


Step 3: Add and subtract the above number after the \(x\) term in the expression whose coefficient of \(x^2\) is \(1\)

\[\begin{align} -4 (x^2\!+\!2x\!+\!3)\!&=\!\!-4 \left(x^2\!+\!2x\! +\color{green}{\mathbf{1 -1}} \!+\!3 \right)\end{align}\]

Step 4: Factorize the perfect square trinomial formed by the first 3 terms using the identity \( x^2+2xy+y^2=(x+y)^2\)

In this case, \[x^2+2x+ 1= (x+1)^2\]

The above expression from Step 3 becomes:

\(-4 \left(\color{green}{x^2\!+\!2x \!+\!1\!}-\!1 \!+3\right)\)=\(-4 (\!\color{green}{(x+1)^2}\!\! -\!1+3\!)\)

Step 5: Simplify the last two numbers.

Here, \(-1+3=2\)

Thus, the above expression is:

\[ -4 (x+1)^2 \color{green}{-1+3} =  -4 ((x+1)^2 +\color{green}{2}) \\= -4(x+1)^2-8\]

This is of the form \(a(x+d)^2+e\).

Hence, we have completed the square.

Thus, \(-4 x^2-8 x-12= -4 (x+1)^2 -8)\) 

Here is the completing the square calculator. We can enter any quadratic expression here and see how the square can be completed..

Solved Examples

Example 1



Can we help Sophia to understand \(x^2\) and \(2x\) don't need to be the same by evaluating them at \(x= -6\)?


It is given that \(x=-6\).


\[\begin{align} x^2 &= (-6)^2 = -6 \times -6 = 36\\[0.2cm]
2x &= 2(-6) = 2 \times -6 = -12 \end{align}\]

Here, \(x^2 \neq 2x\).


\(x^2\) and \(2x\) don't need to be the same
Example 2



Can we help Jim to factorize the following expression using the formula of difference of squares?



The formula of difference of squares says: \[x^2-y^2=(x+y)(x-y)\]

We will apply this to factorize the given expressions as many times as needed.

x^4-16 &= (x^2)^2 - 4^2\\[0.2cm]
&= (x^2+4)(x^2-4)\\[0.2cm]

Therefore, the given expression can be factorized as

Example 3



The area of a square-shaped window is 36 square inches. Can you find the length of the window?

x squared word problem: a square shaped window


Let us assume that the length of the window is \(x\) inches.

Then its area using the formula of area of a square is \( x^2\) square inches.

By the given information, \[x^2 = 36\]

By taking the square root on both sides, \[ \sqrt{x^2}=  \sqrt{36}\]

We know that the square root of \(x^2\) is \(x\).

The square root of 36 is 6 because \(6^2=36\).


\(\therefore\) The length of the window = 6 inches
Example 4



Solve by completing the square.



The given quadratic equation is:


We will solve by completing the square.

Here, the coefficient of \(x^2\) is already \(1\)

The coefficient of \(x\) is \(-10\)

The square of half of it is \((-5)^2 =25\)

Adding and subtracting it on the left-hand side of the given equation after the \(x\) term:

\[ \begin{aligned} x^2-10x+25-25+16&=0\\[0.2cm](x-5)^2-25+16&=0\\ [\because x^2\!-\!10x\!+\!25\!=\! (x\!-\!5)^2 ]\\[0.2cm] (x-5)^2-9&=0\\[0.2cm] (x-5)^2& =9 \\[0.2cm] (x-5) &= \pm\sqrt{9} \\ [ \text{Taking square root }&\text{on both sides} ]\\[0.2cm] x-5=3; \,\,\,\,&x-5= -3\\[0.2cm] x=8; \,\,\,\,&x = 2 \end{aligned} \]

\(\therefore\) \(x=8,\, \, 2\)
Challenge your math skills
Challenging Questions
  1. Solve by completing the square.
    \[x^4-18 x^2+17=0\]
    Hint: Assume \(x^2=t\)
  2. Write the following equation of the form \((x-h)^2+(y-k)^2=r^2\) by completing the square.
    \[x^2+y^2-4 x-6 y+8=0\]
    Hint: Group \(x\) terms separately and \(y\) terms separately and then complete the squares.

Interactive Questions

Here are a few activities for you to practice.

Select/type your answer and click the "Check Answer" button to see the result.


Let's Summarize

The mini-lesson targeted the fascinating concept of x squared. We explored x squared, x squared equals, square root, x cubed, what is x Squared x, x 2,  x squared times x, x squared plus x squared, x squared symbol, x squared minus x, x squared divided by x, and x squared plus y squared.

The math journey around x squared starts with what a student already knows, and goes on to creatively crafting a fresh concept in the young minds. Done in a way that not only it is relatable and easy to grasp, but also will stay with them forever. Here lies the magic with Cuemath. 

About Cuemath

At Cuemath, our team of math experts is dedicated to making learning fun for our favorite readers, the students!

Through an interactive and engaging learning-teaching-learning approach, the teachers explore all angles of a topic.

Be it worksheets, online classes, doubt sessions, or any other form of relation, it’s the logical thinking and smart learning approach that we, at Cuemath, believe in.

Frequently Asked Questions (FAQs)

1. What is a squared minus b squared?

This is given by the difference of squares formula:


2. What does 3 x squared mean?

3 x squared means \(3x^2\).

Its 3 times \(x^2\).

3. How do you type 2 x squared?

2 x squared can be typed as \(2x^2\).

Here, the 2 above \(x\) is a superscript.

4. How do you find square root?

To find the square root of a number, we have to see by multiplying which number by itself, we can get the given number.

For example,

\[ \sqrt{9} = \sqrt{3^2} = 3\]